Old Testament use of Old Testament : a book-by-book guide - Schnittjer, Gary Edward, 1965- (Grand Rapids, MI, Zondervan Academic, 2021)
Old Testament Use of Old Testament, by Gary Edward Schnittjer, surveys the hundreds of Old Testament allusions within the Old Testament and provides hermeneutical guidance for interpreting these interrelated scriptures. The handbook takes an easy to navigate book-by-book approach. Schnittjer provides a list of Scripture allusions for each book and follows with an interpretive profile of how that book uses passages from elsewhere in the Old Testament. Specific criteria are applied to each allusion, providing readers with evaluation of the significance of each interpretive allusion. Minor allusions caused by style, figures of speech, and other minor elements are not included. Responsible exegesis requires careful attention to interrelated scriptures, yet there is a host of interpretive difficulties related to Scripture's use of Scripture. Designed for ease-of-use for any serious student of the Bible, Old Testament Use of Old Testament offers a thorough, systematic tool to aid in evaluating scriptural interpretation of Scripture.
Genesis ; Exodus ; Leviticus ; Numbers ; Deuteronomy ; Joshua ; Judges ; Samuel ; Kings ; Isaiah ; Jeremiah ; Ezekiel ; Hosea ; Joel ; Amos ; Obadiah ; Jonah ; Micah ; Nahum ; Habakkuk ; Zephaniah ; Haggai ; Zechariah ; Malachi ; Psalms ; Job ; Proverbs ; Ruth ; Song of Songs ; Ecclesiastes ; Lamentations ; Esther ; Daniel ; Ezra-Nehemiah ; Chronicles ; Toward the New Testament ; Networks.
Includes bibliographical references and indexes.
Keywords: Bible. -- Criticism, interpretation, etc; Intertextuality in the Bible; Criticism, interpretation, etc